RESPON PERTUMBUHAN DAN PRODUKSI TANAMANJAGUNG (Zea mays L.) VARIETAS HIBRIDA DAN NONHIBRIDAN TERHADAP PEMBERIAN PUPUK POSPAT DAN BOKASHI - Ginting, Eva Sari; Bangun, Mbue Kata; Putri, Lollie Agustina P. (Universitas Sumatera Utara, 2013)
Response on Growth and Yield of Maize (Zea mays L.) Hybrid and Nonhybrid Varieties by Phosphate Fertilizer and Bokashi Application.The goal of this research is to know the effect of phosphate fertilizer and bokashi to growth and yield maize (Zea mays L.) hybrid and nonhybrid varieties.Therefore, a research had been conducted at experimental field of BBI Palawija, Tanjung Selamat, District of Deli Serdang (± 57 m asl) on May – August 2012. This research was arranged using Randomized Block Design, with the first factor is two maize varieties, Bisma and SHS 4. The second factor is concentrate of Phosphate fertilizer with three degrees, 2 g, 4 g and 6 g. The third factor is bokashi with two degrees, 0 g and 180 g, three replications was used to the treatments. Data were analyzed with ANOVA and continued with HSD. The results showed that varieties were significantly different to plant height, leaf number, male flowering time, female flowering time, harvesting time, kernel number per ear and yield of sample. Phosphate fertilizer were significantly effect to leaf number at 2 weeks planted, harvesting time, kernel number per ear and yield of sample. Bokashi were significantly effect to plant height (at 2, 3, 5 and 7 weeks planted), leaf number (at 2 and 5 weeks planted), male flowering time, female flowering time and number of kernel per ear. The combination between varieties and phosphate fertilizer were not significantly different to whole parameters. The combination between varieties and bokashi were significantly different to plant height (at 7 and 8 weeks planted). The combination between phosphate fertilizer and bokashi were significantly effect to plant height at 2 weeks planted and kernel number per ear. Key words : maize, varieties, phosphate fertilizer, bokashi